The Influence of Inquiry Learning Model and Critical Thinking Ability on Student Learning Outcomes - Augustri Ritonga; Rahmad Husein; Widiasih Widiasih (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
This study describes the influence of the inquiry learning model and critical thinking skills on student learning outcomes. The research population was all seventh grade students of SMP Negeri 3 Tarutung. The sample was set at 60 people consisting of 2 (two) classes, with details of class VII-B totaling 30 people, class VII-C totaling 30 people. This research was carried out from October to December 2021. This research instrument used a multiple choice test of 30 items for learning outcomes tests and 10 items in the form of essays for critical thinking ability tests. The research design used in this study was an experimental design with a 2x2 factorial. In this study, the first independent variable consisted of two, namely the inquiry and conventional models. While the second independent variable (moderator variable) consists of high and low critical thinking skills and the dependent variable is science learning outcomes. The results showed that there was an effect of the inquiry learning model on the science learning outcomes of students at SMP Negeri 3 Tarutung of 0.004. There is an effect of critical thinking skills on students' science learning outcomes at SMP Negeri 3 Tarutung of 0.002. There is an interaction between learning models and critical thinking skills on student learning outcomes based on the results of the ANOVA test, the value of sig = 0.022 <sig.0.05. Thus, it can be concluded that there is an interaction between learning models and critical thinking skills in influencing student learning outcomes.